Community Empowerment Governance for Ex-Terrorists: Deradicalization Efforts Through Social Capital - Tando, Cahyoko Edi; Biafri, Vivi Sylviani; Aulia, Qisthina (Jurnal Borneo Administrator, 2025)
Terrorism is an extraordinary crime that has a profoundly negative impact on society,with the Cirebon area having the highest red-zone level in West Java Province. Thisregion is highly vulnerable to the spread of radical ideologies and terrorist activitieswithin the community. Ex-terrorists get difficulty in finding job after imprisonmentand face negative stigma from the society. Therefore, community governancethrough empowerment of ex-terrorists is required. The research employs a qualitativemethod, collecting data through interviews with six informants. The results of thisstudy indicate that, according to social capital theory, which encompasses threedimensions, the process for ex-terrorist convicts involves soft-power strategies in theform of microeconomic empowerment conducted by the Social Identification(Idensos) Team and the Class 1 Probation Office (Bapas) in Cirebon. This approachis applied because all of them are members of JAD, which has low economicconditions. The second dimension, bridging, involves these former convicts activelyparticipating in community service activities, remaining open, and no longerisolating themselves as part of efforts to eliminate societal stigma. The thirddimension, linking, involves collaboration with private companies in the agriculturalsector, including mentorship for agricultural activities. Looking forward, challengesidentified include the lack of local regulations in Cirebon aimed at preventingterrorism and post-sentence rehabilitation, as well as the limited presence of counterterrorism activities in the media. These two challenges could provide useful input for future research.